1991
DOI: 10.1093/oxfordjournals.eurheartj.a059929
|View full text |Cite
|
Sign up to set email alerts
|

Clinical presentation and prognosis of left main coronary artery disease in the 1980s

Abstract: Clinical presentation and course were studied in 127 consecutive patients with angiographically proven left main coronary artery disease. Mean age was 62 (37-79) years. Thirteen patients (10%) had no history of chest pain, seven (5%) had atypical chest pain, and the remaining 107 (85%) typical angina pectoris. Eighty-two patients (65%) had unstable angina, 73 had suffered a myocardial infarction (MI) in the past, and 50 (68%) had post MI angina pectoris. The electrocardiogram was analysed in 102/125 patients d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
17
0

Year Published

1992
1992
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 22 publications
2
17
0
Order By: Relevance
“…In a recent CCA study, significant LMCAD, and nonsignificant LMCAD were found in 4.8% and 3.3% of 17323 patients, respectively [16]. Similar results were obtained for significant LMCAD prevalence in previous studies [17,21]. The relatively lower prevalence of significant LMCAD (2.4%) that was found in our study may be due to the lower risk profile of patients referred to MSCT examinations.…”
Section: Discussionsupporting
confidence: 88%
“…In a recent CCA study, significant LMCAD, and nonsignificant LMCAD were found in 4.8% and 3.3% of 17323 patients, respectively [16]. Similar results were obtained for significant LMCAD prevalence in previous studies [17,21]. The relatively lower prevalence of significant LMCAD (2.4%) that was found in our study may be due to the lower risk profile of patients referred to MSCT examinations.…”
Section: Discussionsupporting
confidence: 88%
“…Nearly half of the former had typical chest pain before the acute event [5]. An isolated left main coronary stenosis in the great majority of cases is due to coronary heart disease [1]. External compression by a malignancy may be the most important among the rare causes of left main stenosis, such as inflammatory vessel disease [10], mediastinal irradiation [8], and a muscle bridge.…”
Section: Discussionmentioning
confidence: 99%
“…P rior studies have demonstrated that STsegment elevation (STE) in electrocardiographic (ECG) lead aVR in the setting of acute coronary syndromes may indicate the presence of severe stenosis or occlusion of the left main coronary artery (LMCA) or proximal left anterior descending coronary artery (LAD) (1)(2)(3)(4)(5)(6)(7)(8)(9)(10). Data reSee page 187 garding the significance of STE in lead aVR in the setting of exercise treadmill testing (ETT), however, are limited.…”
mentioning
confidence: 99%